Legal Aspects of Regional Development Financing Through Issuance of Local Bonds - R. Sugiharto; Andi Aina Ilmih; A. Zulkarnain (Budapest International Research and Critics University, 2022)
This study focuses on financing regional development through the issuance of regional bonds. By analyzing regional bonds as a source of financing for infrastructure development in the region, thus encouraging researchers to conduct in-depth studies of the legal regulation of regional bonds as a source of regional financing and things that have the potential to become obstacles in the issuance and trading of regional bonds as a source of development financing. area. This research is an empirical juridical research. Sources of research data are primary and secondary data. Data analysis used descriptive qualitative analysis method. The results of this study indicate that the legal and policy arrangements related to Regional Financing through the Issuance of Regional Bonds are contained in the PERMENKEU RI Number 180/PMK.07/2015 concerning Amendments to the PERMENKEU RI Number 111/PMK.07/2012 concerning Issuance Procedures and Accountability Regional Bonds. Things that have the potential to become obstacles in the issuance and trading of regional bonds, namely: normative factors and empirical factors. First, the normative factor is caused by disharmony between laws and regulations. Second, empirical factors related to the institutional relationship between the central and local governments related to the existence of administrative requirements before the issuance of regional bonds that must be fulfilled and; 2) related to the availability of Human Resources who still have limited understanding in the management of regional bonds.